PENGARUH SEGMENTASI PASAR TERHADAP KEPUTUSAN PEMBELIAN PADA OUTLET SAHABAT RPK UMI DI TERMINAL PASAR BUMI HARAPAN TOLITOLI - Fitriyah Astri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aimed to determine the Influence of Market Segmentation on purchasing decisions Outlet Sahabat RPK Umi. In this study, This study using a quantitative approach with the type of descriptive research, the tool used for testing this research is Statistical Product and Service Solution (SPSS) V. 20 and data were collected using the tools of observation, interviews and questionnaires to 75 respondents using purposive sampling technique, which aims to determine the respondents perceptions of each variable. The analysis used includes the data instrument test (validity test and reliability test), The results,researchers suggest that. The results,researchers suggest, from the analysis using regression, it can be seen that the market segmentation have a positive effect on purchasing decisions.